2018
DOI: 10.1177/1073110518782943
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Civil Commitment in the Opioid Crisis

Abstract: This article seeks to shed light on civil commitment in the context of the opioid crisis, to sketch the existing legal landscape surrounding civil commitment, and to illustrate the relevant medical, ethical, and legal concerns that policymakers must take into account as they struggle to find appropriate responses to the crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Strategies employing outright deception or forceful coercion directly undermine patients' autonomy and trust in the doctor-patient relationship, and should be confined to those circumstances in which patients are determined to lack capacity and are at serious, immediate risk. While few of the interviewees in our study reported that they would resort directly to paternalistic measures, it is worth noting that a number of states have proposed legislation that may require EPs to do exactly that, such as imposing involuntary 72-h holds within the ED for any patients presenting with an overdose (22,45). Notably, these mandates rarely come with the support of additional resources or legal protections for the physicians tasked with carrying them out.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Strategies employing outright deception or forceful coercion directly undermine patients' autonomy and trust in the doctor-patient relationship, and should be confined to those circumstances in which patients are determined to lack capacity and are at serious, immediate risk. While few of the interviewees in our study reported that they would resort directly to paternalistic measures, it is worth noting that a number of states have proposed legislation that may require EPs to do exactly that, such as imposing involuntary 72-h holds within the ED for any patients presenting with an overdose (22,45). Notably, these mandates rarely come with the support of additional resources or legal protections for the physicians tasked with carrying them out.…”
Section: Discussionmentioning
confidence: 87%
“…A set of a priori codes reflecting potential ethical and practical challenges to treating patients after an opioid overdose within the ED was created by the study investigators based on review of the existing emergency medicine and clinical ethics literature on opioid use, opioid use disorder (OUD), and informed refusal (13,20,22,23). This process was supplemented by conversations with colleagues with expertise in medical toxi-cology and addiction psychiatry.…”
Section: Primary Data Analysismentioning
confidence: 99%
“…Another report has pointed out that, in the US, "constitutional and other legal rules governing civil commitment were not developed in the context of SUD, and did not anticipate application to individuals with SUD. Nor have the statutory standards for civil commitment been developed in contemplation of the medically appropriate treatment for SUD, which is most often a combination of medication assisted treatment and psychosocial treatment" (Bhalla et al, 2018). This suggests that changes in state laws about the use of civil commitment of those with SUD are being critically considered on medical, ethical, and legal grounds, as well as competing for social and liberties interests.…”
Section: Us Efforts To Reduce Opioid Usementioning
confidence: 99%
“…12 Aside from the obvious civil liberty concerns, patients committed under these systems face dramatically higher risk of relapse and overdose than those re-entering the community from voluntary treatment. 13 For instance, according to Massachusetts Department of Public Health data, patients re-entering the community from a period of civil commitment for SUD face 2.2 times the risk of fatal overdose compared to those completing a course of voluntary treatment, and a recent study reported that one third of people with SUD who were civilly committed in MA used drugs on the day they were released. 14 These data echo international evidence that compulsory treatment is a source of risk, rather than risk reduction.…”
Section: Ineffective and Counterproductive State Policiesmentioning
confidence: 99%